Immunological alterations in individuals exposed to metal(loid)s in the Panasqueira mining area, Central Portugal - Coelho, P. (2015)
Environmental studies performed in Panasqueira mine area (central Portugal) identified high concentrations of several metal(loid)s in environmental media, and individuals environmentally and occupationally exposed showed higher levels of As, Cr, Mg, Mn, Mo, Pb and Zn in blood, urine, hair and nails when compared to unexposed controls. To evaluate the presence of immunological alterations attributable to environmental contamination, we quantified neopterin, kynurenine, tryptophan, and nitrite concentrations in plasma, and analysed the percentage of several lymphocytes subsets, namely CD3+, CD4+ and CD8+ T-cells, CD19+ B-cells, and CD16+56+ natural killer (NK) cells in a group of individuals previously tested for metal(loid) levels in different biological matrices. The environmentally exposed group had significantly lower levels of %CD8+ and higher CD4+/CD8+ ratios, whereas the occupationally exposed individuals showed significant decreases in %CD3+ and %CD4+, and significant increases in %CD16+56+, when compared to controls. Analysed biomarkers were found to be influenced by age, particularly neopterin, kynurenine and kynurenine to tryptophan ratio (Kyn/Trp) with significantly higher levels in older individuals, and %CD3+, %CD8+ and %CD19+ with significantly lower values in older individuals. Males environmentally exposed showed significantly lower values of %CD19+ when compared to control females. The concentration of Pb in toenails was associated to the level of neopterin, kynurenine and Kyn/Trp ratio (all direct), and the concentration of Mn in blood to the level of %CD8+, %CD19+ (both inverse) and CD4+/CD8+ ratio (direct). Overall our results show that the metal(loid) contamination in Panasqueira mine area induced immunotoxic effects in exposed populations, possibly increasing susceptibility to diseases.